2004
DOI: 10.1007/s00268-004-7214-x
|View full text |Cite
|
Sign up to set email alerts
|

Procedures of Choice for Resection of Primary and Recurrent Liver Metastases from Colorectal Cancer

Abstract: Although liver resection offers the only realistic chance of cure for patients with liver metastases from colorectal cancer, no consensus exists as to the procedure of choice for managing these tumors. Data from 193 patients who underwent hepatectomy for liver metastases from colorectal cancer and 26 of 193 patients who underwent repeat hepatectomy for recurrent metastases were collected. The suitability of resection was evaluated retrospectively based on known risk factors for recurrence and patterns of recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 41 publications
4
23
1
4
Order By: Relevance
“…Martin et al [10] observed increased positive margin rate in wedge excisions and advocate anatomic hepatectomies. This view is shared by Tanaka et al [26] . Bilateral subcostal incision provides excellent liver exposure and facilitates colon resection from the cecum up to the descending colon.…”
Section: T H I S a P P R O A Ch Wa S Awa R D E D W I T H A M O R T A supporting
confidence: 73%
See 2 more Smart Citations
“…Martin et al [10] observed increased positive margin rate in wedge excisions and advocate anatomic hepatectomies. This view is shared by Tanaka et al [26] . Bilateral subcostal incision provides excellent liver exposure and facilitates colon resection from the cecum up to the descending colon.…”
Section: T H I S a P P R O A Ch Wa S Awa R D E D W I T H A M O R T A supporting
confidence: 73%
“…Expertise in liver resections is an important factor in determining patient outcome, since the majority of postoperative morbidity and mortality are mainly related to liver surgery, a point that has been established by many studies [4,10,18,[24][25][26] . Bleeding during hepatectomy is a poor prognostic factor and all efforts should be centered at minimizing blood loss by meticulous techniques and liver vascular control [1][2][3]10,23] .…”
Section: T H I S a P P R O A Ch Wa S Awa R D E D W I T H A M O R T A mentioning
confidence: 99%
See 1 more Smart Citation
“…The liver is the most common site of recurrence and might be the only site of recurrence in about one third of those who recur. 4,[56][57][58] Repeated hepatectomy for recurrence is becoming more frequent due to early detection, new chemotherapeutic agents, accumulating experience with liver parenchyma sparing resections and due to the use of new powered instruments. Prognostic factors and surgical goals that apply to the initial liver resection for CRC metastases apply to repeat hepatectomies as well.…”
Section: Surgical Techniques and Management Strategiesmentioning
confidence: 99%
“…Die Re-Resektion kann mit der gleichen Sicherheit und mit vergleichbaren 5-JahresÜberlebensraten durchgeführt werden wie die primäre Metastasenresektion. Die 5-Jahres-Überlebensraten liegen hier zwischen 23 und 49 % [193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210][211]. Auch nach Drittresektion kann ein 5-Jahres-Überleben von 32 % und ein krankheitsfreies Überleben von 17 % erreicht werden [193].…”
Section: Vorgehen Bei Rezidiv-metastasenunclassified